Building a dynamic team : a practical guide to maximizing team performance - Chang, Richard Y. (Jossey-Bass Pfeiffer San FranciscoUS, 1994)
Provides guidelines for any stage of team development. Examines the elements of a dynamic team, and identifies the phases of development as driving, striving, thriving and arriving. Looks at topics including: mapping out the team's mission statement; roles and responsibilities of team members; decision making; and, maintaining top performance. Includes worksheets, and a dynamic team assessment instrument.